Cerebral Vasospasm Affects Arterial Critical Closing Pressure. Issue 2 (February 2015) - Varsos, Georgios V; Budohoski, Karol P; Czosnyka, Marek; Kolias, Angelos G; Nasr, Nathalie; Donnelly, Joseph; Liu, Xiuyun; Kim, Dong-Joo; Hutchinson, Peter J; Kirkpatrick, Peter J; Varsos, Vassilis G; Smielewski, Peter
The effect of cerebral vasospasm (CVS) after aneurysmal subarachnoid hemorrhage (SAH) on critical closing pressure (CrCP) has not been fully delineated. Using cerebral impedance methodology, we sought to assess the behavior of CrCP during CVS. As CrCP expresses the sum of intracranial pressure (ICP) and vascular wall tension, we also explored its role in reflecting changes in vascular tone occurring in small vessels distal to spasm. This retrospective analysis was performed using recordings from 52 patients, diagnosed with CVS through transcranial Doppler measurements. Critical closing pressure was calculated noninvasively using arterial blood pressure and blood flow velocity. Outcome was assessed at both discharge and 3 months after ictus with the Glasgow Outcome Scale. The onset of CVS caused significant decreases in CrCP ( P =0.025), without any observed significant changes in ICP ( P =0.134). Vasospasm induced asymmetry, with CrCP ipsilateral to CVS becoming significantly lower than contralateral ( P =0.025). Unfavorable outcomes were associated with a significantly lower CrCP after the onset of CVS (discharge: P =0.014; 3 months after SAH: P =0.020). Critical closing pressure is reduced in the presence of CVS in both temporal and spatial assessments. As ICP remained unchanged during CVS, reduced CrCP most probably reflects a lower wall tension in dilated small vessels distal to spasm.